GE_GERICHTE C/6764/2016 vom 9. März 2018 - GE Cour de justice (2018)
CLASSEMENT DE LA PROCÉDURE ; POURSUITE POUR DETTES ; PROMESSE DE DONNER ; FRAIS(EN GÉNÉRAL) | LP.85A.al1; CO.250.al1.ch2; CO.516.al1